CYBER-COLLECTIVE ACTION NETIZEN MELALUI MEDIA SOSIAL TWITTER DENGAN HASTAG #SHAMEONYOUSBY - Hinggarwati, Fat'khah Dwi (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2016)
Abstract :People use social media to communicate with others, including to give an opinions. And in this way netizen on Indonesia in givingÂ his opinion. Netizen in Indonesia giving a protest against the government through social media twitter. They wrote the disappointment tweetwith hastag #ShameOnYouSBY. This research use qualitative descriptive analysis, and discuss about the form of cyber-collective action that occurs in a protest the netizen, andÂ how social media activismÂ get the support. Of research results, obtained four stages cyber-collective action that is the individual perspective, group perspective, national perspective, and transnational perspective.In addition, social media activist also uses the principle of consumption of contemporary culture in seeking the support of the masses from social media twitter.Keywords: Social Media, twitter, cyber-collective action, activist